The self-sufficiency of the political order in Dante Alighieri - Abbate, Stefano (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The aim of this article is to retrace the fundamental premises of Dante’s political thought, which posits a new conception of the relationship between Church and Empire. In particular, three fundamental ideas are pointed out: science as the ultimate perfection of the human soul; the proper operation of the human race in the action of all the possible power of the intellect; and finally the question of the natural and supernatural purpose of man. Secondly, the presence of the interpretation of Aristotelianism of the Faculty of Arts of the University of Paris and of Averroism in the Dantesque approach is analysed, in particular with reference to the different interpretations of Gilson and Nardi. Finally, the question of the transfer of the keys from Jesus to Peter and the relationship between nature and grace in dissonance with the interpretation of Thomas Aquinas are proposed as a key to the overall interpretation of Dantesque political thought.
Keywords: Dante; Church; Empire; Averroism; Aristotelianism